Engaging the enemy : organization theory and Soviet military innovation, 1955-1991 - Marten, Kimberly Zisk, 1963- (Princeton, N.J. : Princeton University Press, 1993)
Did a ""doctrine race"" exist alongside the much-publicized arms competition between East and West? Using recent insights from organization theory, Kimberly Marten Zisk answers this question in the affirmative. Zisk challenges the standard portrayal of Soviet military officers as bureaucratic actors wedded to the status quo: she maintains that when they were confronted by a changing external security environment, they reacted by producing innovative doctrine. The author's extensive evidence is drawn from newly declassified Soviet military journals, and from her interviews with retired high-
Book Cover; Title; Copyright; Contents
Includes bibliographical references (pages 251-280) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Military doctrine -- Soviet Union; Doctrines militaires -- URSS; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Military doctrine; Soviet Union; Defence (Military strategy); Union of Soviet Socialist Republics; Electronic book